Applicability of Paper and Pulp Industry Waste for Manufacturing Mycelium-Based Materials for Thermoacoustic Insulation - Vasco-Calle, D; Urzua-Parra, I (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Cellulose and paper produce significant waste such as ash, activated sludge, and sludge from the pulp and paper industry. Depending on the raw material, legislation, and subprocesses, these sludges contain around 30–50% organic matter, mainly composed of less than 0.02 mm cellulose fibers and hemicellulose and lignin. This work used sludge from the pulp and paper industry as a substrate for manufacturing mycelium-based biomaterials using the white rot fungus Trametes versicolor. Chemical and surface analyses revealed the formation of new materials. Acoustic impedance analyses revealed that these materials have a noise reduction coefficient and sound absorption average comparable to extruded polystyrene and polyurethane. In addition, the material’s thermal conductivity was near that of sheep wool. Therefore, the biomaterials fabricated using sludge and Trametes versicolor have the potential to be a game-changer in the industry as promising thermoacoustic insulators. © 2024 by the authors.